Mist cooling for the electric card - Lam, Yan Feng (2015)
With the evolution of technology such as integrated chips on electric card, better heat dissipation techniques are demanded to cope with the increased power density. Traditionally, air or water cooling solutions were utilized. However, these methods are soon unable to keep up with the new requirements, resulting in the development of novel solutions such as the proposed mist-cooling method. In recent years, experiments have been conducted to explore the parameters and capabilities of mist cooling. In this project, an investigation on the effects of coolant pressure on heat dissipative ability was conducted on a flat plate in a confined chamber. The flat plate serves as a model for an integrated chip board. Surface temperature of the plate was measured under different power and pressure setting during the process. The aim of the experiment is to determine the optimized pressure of coolant to cool down the system. The result shows a decrease of 4 to 6 degree Celsius in temperature under different coolant pressures used. With a higher coolant pressure, the final equilibrium temperature of the heated plates is reduced, and also heat transfer coefficient, increases. The overall results gathered from this study suggest that mist cooling will be able to cope with wattage even higher than current CPUs. This method can help surpass the current limitations that computer engineers face. However, this study is still in the initial phase, more studies are needed to better quantify and experiment with the parameters relevant to heat transfer. In addition, to make this a working solution, further research and development has to be made in commercializing this product.